Respuesta :
Answer:
Interest earned = 2713.8
Explanation:
We will solve this problem on two steps:
1- get the final amount after three years
2- get the interest earned by subtracting the initial amount from the final one.
1- getting the final amount after 3 years:
The formula that we will use is as follows:
A = P (1 + r/n)^(nt)
where:
A is the final amount we want to calculate
P is the initial amount = 6300
r is the interest = 0.12
n is the number of compounds per year =12
t is time in years = 3
Substitute to get the final amount:
A = P (1 + r/n)^(nt)
A = 6300 (1 + 0.12/12) ^ (12*3)
A = 9013.8
2- getting the interest earned:
Interest earned = final amount - initial amount
Interest earned = 9013.8 - 6300
Interest earned = 2713.8
Hope this helps :)
Interest earned = 2713.8
Explanation:
We will solve this problem on two steps:
1- get the final amount after three years
2- get the interest earned by subtracting the initial amount from the final one.
1- getting the final amount after 3 years:
The formula that we will use is as follows:
A = P (1 + r/n)^(nt)
where:
A is the final amount we want to calculate
P is the initial amount = 6300
r is the interest = 0.12
n is the number of compounds per year =12
t is time in years = 3
Substitute to get the final amount:
A = P (1 + r/n)^(nt)
A = 6300 (1 + 0.12/12) ^ (12*3)
A = 9013.8
2- getting the interest earned:
Interest earned = final amount - initial amount
Interest earned = 9013.8 - 6300
Interest earned = 2713.8
Hope this helps :)
Answer: There will be $2,713.84 earned in interest.
This is an example of an exponential equation. It is in the form of y = ab^x. We just have to insert the start, rate and time.
Our equation would be: y = 6300(1 + 0.12/12)^(3 x 12)
You have to be careful to divide the rate by 12 and multiply the years by 12 because it is compounded monthly.
Total will be $9,013.84 minus the starting investment of $6,300 leaves $2,713.84 in interest.
This is an example of an exponential equation. It is in the form of y = ab^x. We just have to insert the start, rate and time.
Our equation would be: y = 6300(1 + 0.12/12)^(3 x 12)
You have to be careful to divide the rate by 12 and multiply the years by 12 because it is compounded monthly.
Total will be $9,013.84 minus the starting investment of $6,300 leaves $2,713.84 in interest.